Ecotourism based on the observation of sea turtles: a sustainable solution for the touristic promotion of São Tomé and Príncipe - Mendes, Susana (2020)
Wildlife-based ecotourism has been stated as an efficient tool to promote the conservation of endangered species and habitats. These activities also aim to create economic revenue for local communities. Likewise, ecotourism, intends to involve these communities in the management of the conservation programs and develop educational activities, either for children, locals, or tourists, in order to increase awareness about target species and habitats. This study addressed the recent ecotourism activities in the observation of sea turtles which are being developed in São Tomé and Príncipe. These charismatic marine reptiles are vulnerable or endangered due to human activities, such as meat and egg consumption, illegal trade, habitat loss, climatic change, pollution and fisheries bycatch. Therefore, ecotourism using flagship species, like sea turtle, establishes a sustainable alternative to destructive activities, promoting the country’s environmental, economic and social development, the three pillars of sustainability. In this context, the objective of this study is to know the potential of São Tomé and Príncipe as a turtle watching-based ecotourism destination. An exploratory analysis was carried out through two questionnaires (one focused to the Morro Peixe’s local community and another to the tourists that were engaged in turtle watching activities), in order to know the perception of the inhabitants and tourists regarding the programs and initiatives for the conservation of sea turtles. Despite the awareness that already exists among inhabitants regarding the conservation of sea turtles, the results showed that they do not straightforwardly accept the prohibition for the capture of sea turtles, but most of the population of Morro de Peixe is receptive to changes in the community regarding their protection. In fact, the population is beginning to recognize that tourism, due to the protection given to these endangered species, may become (in the medium term) a sustainable source of income. Regarding tourists’ profile, these are mostly Portuguese, with a high level of education and income. They are well informed about the need for sea turtle conservation and seek to carry out tourism activities that pursue this protection. In fact, this also demonstrates the potential the country has as a turtle watching-based ecotourism destination.